A qualitative study of vaccination behaviour amongst female Polish migrants in Edinburgh, Scotland. Issue 20 (6th May 2019) - Gorman, D.R.; Bielecki, K.; Willocks, L.J.; Pollock, K.G.
Abstract: Vaccine hesitancy is increasing and failure to vaccinate is well-recognised in Europe as a contributing factor to outbreaks of infectious diseases. In Lothian and Scotland, low vaccine uptake has been seen in migrants – notably in the Polish group who have arrived since 2004. The recent Vaccine Confidence in European Union report highlights a concerning recent decline in vaccine confidence in Poland. We held three focus groups containing 13 Polish women about the childhood vaccination programme in Lothian, with specific focus on influenza and Human Papillomavirus vaccinations. Key emergent themes were: trust in the national vaccination policy, trust in the vaccination providers (health professionals), trust in the individual vaccines, balancing the risk of disease, and language and communication. Polish norms, beliefs and behaviours shape how Polish migrants navigate the UK health system and its vaccination programme. While not confident in the Scottish primary care model and its generalist practitioners, the participants liked the ethos of informed consent in Scotland and compared this favourably with the compulsory vaccination policy in Poland. There was a belief that vaccines in Scotland were of higher quality than Poland and with fewer adverse effects. Respondents reported returning to Poland for specialist clinical appointments and diagnostic testing. They regularly access Polish clinical expertise and their opinions about health are influenced by Polish friends and family. They say they have difficulty finding official UK Government and health authority vaccination material and often access Polish media, online resources and information. They are familiar with anti-vaccination activities in Poland. Consequently, there are important unmet information needs for this group of parents who may not be making truly informed choices about vaccination. This requires further investigation especially as migration continues and declining immunisation uptake is reported in many countries across Europe.